A Clinical Study on Correlation of Fungal Infection in Diabetic Foot Ulcer and Its Management - Balaji, Dipen; Bharathi, K.; Toufiq H, Noor; M, Ganesan (Journal of Neonatal Surgery, 2025)
Background: Over the past two decades, diabetes mellitus has surged globally, increasing from 30 million to 177 million cases. A key complication is diabetic foot ulcers (DFU), caused by hyperglycemia-induced neuropathy and poor circulation, often leading to infection and amputation. While bacterial DFU infections are well documented, fungal involvement remains understudied. This study assessed the prevalence of fungal species, especially Candida, in DFUs and compared healing outcomes between debridement alone and debridement with clotrimazole. Methodology: This prospective study at Meenakshi Medical College Hospital (Nov 2022–Apr 2024) included 80 diabetic patients with foot ulcers selected by purposive sampling. Exclusions were non-diabetic ulcers, cellulitis, and gangrene. Data collected included demographics, ulcer grading, and lab values (HbA1c, FBS, PPBS). Tissue samples were examined via KOH mount and cultured on Sabouraud Dextrose Agar. Patients with fungal DFU were randomized to receive either debridement alone or debridement with topical clotrimazole. Results: Fungal infections were detected in 27.5% of DFU cases, with Candida albicans being the most prevalent isolate. No significant association was found between fungal DFU and demographic or lifestyle factors, such as age, gender, or socioeconomic status. However, fungal DFUs were significantly associated with longer duration of diabetes, prolonged ulceration, and poor glycemic control (p < 0.05). Healing outcome is higher in debridement with tropical clotrimazole. Conclusion: Poor glycemic control and long-standing diabetes are major risk factors for fungal infections in DFU. Early detection of fungal involvement and optimal blood sugar management are crucial in preventing complications. Demographic variables were not significantly linked to fungal DFUs, reinforcing the importance of metabolic control in diabetic wound care.